Effect and Analysis of Bacterial Lysates for the Treatment of Recurrent Urinary Tract Infections in Adults - Ricardo E. Ahumada-Cota; Ulises Hernandez-Chiñas; Feliciano Milián-Suazo; María E. Chávez-Berrocal; Armando Navarro-Ocaña; Daniel Martínez-Gómez; Genaro Patiño-López; Erika P. Salazar-Jiménez; Carlos A. Eslava (Pathogens, 2020)
Urinary tract infection (UTI) is a relevant public health problem, economically and socially affecting the lives of patients. The increase of antimicrobial bacterial resistance significantly hinders the treatment of UTIs, raising the need to search for alternative therapies. Bacterial lysates (BL) obtained from Escherichia coli and other pathogens have been used to treat different infectious diseases with promising results. This work aims to evaluate the effect and composition of an autologous BL for the treatment and control of recurrent UTIs in adults. The results show remission in 70% of the patients within the first three months after the administration of BL, while the infection is maintained under control for 6−12 months. The analysis by liquid chromatography−mass spectrometry (LC-MS) of the BL fractions recognized by the sera of patients shows the presence of cytosolic proteins, fimbriae, OMPs, and LPS. Our study demonstrates that the autologous BL contributed to the treatment and control of recurrent UTIs in adults, and its composition shows that different surface components of E. coli are potential immunogens that could be used to create a polyvalent protective vaccine.